Fluorimetric determination of d-amino acid oxidase - Verity, M. Anthony (1967)
1. A sensitive fluorimetric procedure for the assay of d-amino acid oxidase has been developed. 2. The method depends on the formation of a fluorescent derivative, 2-hydroxy-3-methylquinoxaline, on condensation of pyruvate with o-phenylenediamine in acid medium. 3. 2-Hydroxy-3-methylquinoxaline fluoresces strongly in 50% (v/v) sulphuric acid after excitation at 375mμ. A single emission peak is observed at 480mμ. 4. Formation of the quinoxaline is dependent on time, temperature, acidity and relative concentration of reactants. 5. A particulate preparation from mouse kidney required FAD for optimum activity at pH8·5; K(m) was 3·8×10(−3)m; K(FAD) was 1·4×10(−7)m and the reaction was strongly inhibited by p-chloromercuribenzoate and phenylmercuric acetate. 6. Subcellular fractionation on a sucrose density gradient confirmed that the d-amino acid oxidase was localized on small granules.